Sobre Arij Ouweneel y Simon Miller (comps.), The Indian Community of Colonial Mexico. Fifteen Essays on Land Tenure, Corporate Organizations, Ideology and Village Politics - Menegus Bornemann, Margarita (El Colegio de México, A.C., 1992)
-